PERAN PENDEKATAN SISTEM DALAM TRANSFORMASI DIGITAL DI DUNIA PENDIDIKAN - Fattah Nasution, Abdul; Rambe, Afrizal; Oktapianingsi, Rama; Jannah, Aulia (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2024)
The role of system approaches in the digital transformation of education is crucial in ensuring the effective integration of technology into the educational system. This article employs a literature review method, analyzing various sources such as journals, books, articles, and research reports that discuss the impact and challenges of digital transformation in education. It identifies key components of system approaches within educational settings, including human resources, processes, and technology, and how these components interrelate to achieve quality education. Challenges such as digital skills gaps, access inequality, and resistance to change are discussed. Moreover, strategic management in education is emphasized as a systematic approach to improving education quality, with a focus on technological integration, curriculum adaptation, and collaborative efforts among stakeholders. This comprehensive system approach is essential for overcoming barriers and advancing the digital transformation of education, ensuring that it meets the needs of the 21st century. Keywords: Education System, Digital Transformation, Education